Advocacy Aspects in "Interpretation of the Glorious Qur'an" By Dr. Fadl Abbas: Surah Ibrahim as an Application - Abdul Rahman, Ibtihaj Radi (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: This study aims to introduce the “Interpretation of the Glorious Qur’an” by Dr. Fadl Abbas, by showing the most important advocacy aspects in Surat Ibrahim, peace be upon him, through interpretation, with examples of these from our contemporary reality. Methods: The study employs the descriptive approach; It dealt with advocacy in Surat Ibrahim, and the analytical approach in presenting the sayings of the commentators. Results: According to the study, The book "Interpretation of the Glorious Qur'an" is the best witness to da'wah aspects. That is because His Eminence Dr. Fadl Abbas - may God have mercy on him - is one of the divine masters who call to God Almighty because the Sheikh is one of those who combined science and experimental advocacy. Almost all of his writing are in the Service of advocacy. Conclusions: The most important advocacy aspects addressed by Dr. Al-Alamah in Surah Ibrahim are: Gratitude as a reason for increased sustenance, the blessings of supplication and security, and the consequences of injustice and deception. These aspects are discussed in three dimensions: the expulsion of believers from their homes due to the word of truth, the incompatibility of injustice and a virtuous civilization, and the consequences of deception.